KESALAHAN PENGGUNAAN BAHASA PADA TEKS DESKRIPSI HASIL KARYA PESERTA DIDIK SMP KELAS VII - Ratna Dewi Purwiyanti; Ika Septiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the types of errors in descriptive writing, including language use, sentence structure, vocabulary, word choice, coherence, and cohesion, as well as the factors causing these errors in the descriptive texts of seventh-grade students at SMP Negeri 3 Satu Atap Sluke, and the efforts made to overcome these language errors. This study is a qualitative descriptive study using content analysis with a sample of descriptive texts written by seventh-grade students at SMP Negeri 3 Satu Atap Sluke. The results of this study are as follows. First, the types of language errors found in the descriptive texts written by seventh-grade students at SMP Negeri 3 Satu Atap Sluke include sentence structure, vocabulary, word choice, coherence, and cohesion. Second, the factors causing language errors in the students' descriptive texts were due to four factors, including: students' lack of mastery of language rules; carelessness in writing; lack of motivation to write; and students' lack of vocabulary. Third, efforts made to overcome language errors in the students' observation reports include: implementing writing lessons using a process-based approach, improving students' mastery of language rules through reading, and increasing writing practice.